Cover Feature: Ultrasmall Gold Nanocluster Based Antibacterial Nanoaggregates for Infectious Wound Healing (ChemNanoMat 9/2019). Issue 9 (19th August 2019) - Ravindran Girija, Aswathy; Balasubramanian, Sivakumar; Bright, Richard; Cowin, Allison J.; Goswami, Nirmal; Vasilev, Krasimir
Abstract : New antimicrobial nanoaggregates containing ultra‐small gold nanoclusters and chitosan have been synthesized by an electrostatic self‐assembly approach. The resulting nanoaggregates show enhanced antibacterial activity against both Gram‐negative Escherichia coli and Gram‐positive Staphylococcus aureus bacterial strains compared to individual components. Furthermore, the nanoaggregates also facilitate rapid wound healing without exhibiting any cytotoxic effects in mammalian cells. More information can be found in the Full Paper by Nirmal Goswami, Krasimir Vasilev et al. onpage 1176 in Issue 9, 2019 (DOI:10.1002/cnma.201900366 ).